Genomic coamplification of CDK4/MDM2/FRS2 is associated with very poor prognosis and atypical clinical features in neuroblastoma patients. Issue 5 (3rd December 2019) - Amoroso, Loredana; Ognibene, Marzia; Morini, Martina; Conte, Massimo; Di Cataldo, Andrea; Tondo, Annalisa; D'Angelo, Paolo; Castellano, Aurora; Garaventa, Alberto; Lasorsa, Vito A.; Podestà, Marina; Capasso, Mario; et al.
Abstract: Neuroblastoma (NB) is the most common extracranial malignant tumor of childhood and is characterized by a broad heterogeneity in clinical presentation and evolution. Recent advances in pangenomic analysis of NB have revealed different recurrent chromosomal aberrations. Indeed, it is now well established that the overall genomic profile is important for treatment stratification. In previous studies, 11 genes were shown to be recurrently amplified ( ODC1, ALK, GREB1, NTSR2, LIN28B, MDM2, CDK4, MYEOV, CCND1, TERT, and MYC ) besides MYCN, with poor survival of NB patients harboring these amplifications being suggested. Genomic profiles of 628 NB samples analyzed by array‐comparative genome hybridization (a‐CGH) were re‐examined to identify gene amplifications other them MYCN amplification. Clinical data were retrospectively collected. We additionally evaluated the association of FRS2 gene expression with NB patient outcome using the public R2 Platform. We found eight NB samples with high grade amplification of one or two loci on chromosome arm 12q. The regional amplifications were located on bands 12q13.3‐q14.1 and 12q15‐q21.1 involving the genes CDK4, MDM2, and the potential oncogenic gene FRS2 . The CDK4, MDM2, and FRS2 loci were coamplified in 8/8 samples. The 12q amplifications were associated with very poor prognosis and atypical clinical features of NB patients. Further functional and clinical investigations are needed to confirm or refute these associations.